Imagery of opportunity: benthic habitat maps in deeper shelf waters (30-200 m) - Gabrielle H. Cummins; Kingsley Griffin; Claude Spencer; Samuel Thompson; Brooke Gibbons; Matthew L. Navarro; Julian Partridge; Tim J. Langlois (Marine Environmental Research, 2026)

Minimal contribution of bioerosion in the deterioration of biodegradable plastics in the marine environment: evidence from laboratory and field experiments - Winnie Courtene-Jones; Matthew Cole; Rachel L. Coppock; Allicia Fullarton; Holly D.L. Scott; Penelope K. Lindeque; Richard C. Thompson (Environmental Pollution, 2026)

Poorly differentiated sarcoma in the axilla of a guinea pig - Brianna Bazel; Aubrey McCulloch; Alexis Thompson; Matthew Scott; Kendall Langsten (Journal of Exotic Pet Medicine, 2026)

Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Vegetation preference and the puzzle of abandonment: high-quality spawning habitat remains unused by Pacific herring (Clupea pallasii) - Jacob T. Dingwall; Jessica Qualley; Matthew Thompson; Sydni Long; Amanda E. Bates (Marine Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A repeated low-dose regimen of MDMA has transient next-day effects on locomotor activity, anxiety-like behavior, and brain serotonin levels, with no effect on anhedonia-like behavior, in both female and male rats - Ava M. Mac; Srinivasu Kallakuri; Alixandria T. Mascarin; Grant W. LeVasseur; Saniya Haq; Matthew M. Moua; Abdul H. Vasiq; Makayla E. Lewis-Gates; Emily J. Thompson-Huber; Matthew J. Baggott; Shane A. Perrine (Psychopharmacology, 2026)

Beyond size and shape: Physicochemical properties of microplastic test materials generated by cryomilling - Lucy Howarth-Forster; Robyn Barrett; Robert Clough; Lisbet Sørensen; Jack Allen; Chris Powell; Richard C. Thompson; Matthew Cole; Michael Wilde (Journal of Hazardous Materials, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Biosecurity investment impacts on highly pathogenic avian influenza control in United States commercial turkey operations - Jada M. Thompson; Kelly Patyk; Victoria Fields; Matthew Branan; Amy Delgado; Kylie Roesler (Preventive Veterinary Medicine, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Drought-induced tree mortality affects the space-use and individual plasticity of an endangered forest carnivore - Marie E. Martin; Rebecca Green; Eric L. McGregor; Sean M. Matthews; Kathryn L. Purcell; Craig M. Thompson (Biological Conservation, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Machine vision-based assessment of fall color changes in apple leaves and its relationship with nitrogen concentration - Achyut Paudel; Jostan Brown; Priyanka Upadhyaya; Atif Bilal Asad; Safal Kshetri; Joseph R. Davidson; Cindy Grimm; Ashley Thompson; Bernardita Sallato; Matthew D. Whiting; Manoj Karkee (Computers and Electronics in Agriculture, 2025)

Materials Learning Algorithms (MALA): Scalable machine learning for electronic structure calculations in large-scale atomistic simulations - Attila Cangi; Lenz Fiedler; Bartosz Brzoza; Karan Shah; Timothy J. Callow; Daniel Kotik; Steve Schmerler; Matthew C. Barry; James M. Goff; Andrew Rohskopf; Dayton J. Vogel; Normand Modine; et al. (Computer Physics Communications, 2025)

Registry versus claims-based index dates for studies of cancer diagnosis in administrative data - Sarah E. Soppe; Sharon Peacock Hinton; Jamie C. Halula; Jennifer L. Lund; Chris D. Baggett; Sandi L. Pruitt; Megan A. Mullins; Ellis C. Dillon; Matthew E. Barclay; Matthew Thompson; Nicholas Pettit; Georgios Lyratzopoulos; et al. (Cancer Causes & Control, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Modeling the impacts of sand placement strategies on barrier island evolution in a semi-enclosed bay system - Davina L. Passeri; Rangley C. Mickey; David M. Thompson; Michael Itzkin; Elizabeth Godsey; Matthew V. Bilskie; Alexander Seymour; Autumn Poisson; Jin Ikeda; Scott C. Hagen (Coastal Engineering, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Growth hormone–deficient Ames dwarf mice resist sarcopenia and exhibit enhanced endurance running performance at 24 months - Matthew J. Johnston; Sharlene G. Rakoczy; LaDora V. Thompson; Holly M. Brown-Borg (GeroScience, 2025)
Ames dwarf mice ( df/df ) live 50% longer than normal littermates due to a genetic defect in growth hormone (GH) signaling. The enhanced longevity of Ames dwarfs has been studied extensively in an endocrinological context of cellular metabolism and increased resistance to oxidative stress (Bartke. World J Mens Health 37(1):19, 8; Bartke 2; BartkeJ Am Aging Assoc 23(4):219, 10; Bartke. World J Mens Health 39(3):454-465, 11; Brown-Borg et al. Nature 384(6604):33-33, 1; Masternak et al. 2018). However, the skeletal muscle system is relatively unexplored, the quality of which dictates metabolic homeostasis, permits movement and exercise, and exerts paracrine effects on other organs (Delmonico and Beck Am J Lifestyle Med 11(2):167-181, 25; Evans et al. GeroScience 46(1):183, 26; Kim and Kim. Endocrinol Metab (Seoul) 35(1):1-6, 15; Masternak et al. 2018). Here, we characterize the fitness capacity and skeletal muscle morphology of Ames mice to determine if previously established longevous effects of GH deficiency extend to skeletal muscle tissue. Mutually exclusive, age-matched cohorts of male Ames mice and wildtype controls performed grip strength, rotarod, and endurance running experiments over 6 months. The largest difference in physical performance was observed in endurance running capacity, where dwarf mice outperformed wildtype controls increasingly with age. Tibialis anterior (TA) muscles were evaluated for myofiber size, quality, and environment. Ames mice show reduced myofiber cross-sectional area (CSA) paired with increased myofibers per muscle. Dwarf myofiber populations are less heterogenous in size and seemingly resist sarcopenia, as skeletal muscle from aged individuals shows youthful morphological resemblance in mean myofiber CSA, size frequency distribution, and presence of fibrotic tissue. Declines in fitness performance and myofiber integrity were observable in age-matched wildtype controls. Utilizing an established longevity model to investigate skeletal muscle function and morphology is a novel approach to gaining insight into the seemingly inverse relationship between GH signaling and mammalian longevity.

Global vegetation zonation and terrestrial climate of the warm Early Eocene - Nick Thompson; Ulrich Salzmann; David K. Hutchinson; Stephanie L. Strother; Matthew J. Pound; Torsten Utescher; Julia Brugger; Thomas Hickler; Emma P. Hocking; Daniel J. Lunt (Earth-Science Reviews, 2025)

Reply to “timing errors in global sea level observations” (Pan et al., 2025) - Philip R. Thompson; Ayesha S. Genz; Matthew J. Widlansky; Gary T. Mitchum; Elizabeth Bradshaw; Adam T. Devlin; Begoña P. Gómez; Ivan D. Haigh; Marta Marcos; Andrew Matthews; Mark A. Merrifield (Ocean Dynamics, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

The effects of carbonate contamination on Ni-Cu-PGE deposit genesis in the Platreef, northern Bushveld Complex: A case study using Niggli numbers - Erin S. Thompson; David A. Holwell; Iain McDonald; Marc Reichow; Thomas G. Blenkinsop; Hannah S.R. Hughes; Katie McFall; Kate R. Canham; Matthew A. Loader; Lara Du Preez; Kofi Acheampong; Andy Lloyd (Chemical Geology, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Small volume solid phase extraction method for comprehensive analysis of neonicotinoids, their metabolites, and related pesticides in water - Wenjing Xi; Sarah Onysio; James Kacer; Matthew Nagorzanski; Hanseob Shin; David M. Cwiertny; Darrin A. Thompson (Science of The Total Environment, 2024)

The cost of operational complexity: A causal assessment of pre-fire mitigation and wildfire suppression - Jesse D. Young; Erin Belval; Benjamin Gannon; Yu Wei; Christopher O'Connor; Christopher Dunn; Bradley M. Pietruszka; David Calkin; Matthew Thompson (Forest Policy and Economics, 2024)

Predictors of long-term variability in NE Atlantic plankton communities - Matthew M. Holland; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Eric Goberville; Pierre Hélaouët; Margarita Machairopoulou; Matthew Faith; Murray S.A. Thompson; Abigail McQuatters-Gollop (Science of The Total Environment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Scaling of soil organic carbon in space and time in the Southern Coastal Plain, USA - Rajneesh Sharma; Matthew R. Levi; Matthew C. Ricker; Aaron Thompson; Elizabeth G. King; Kevin Robertson (Science of The Total Environment, 2024)

Synthesis of proton-conductive Perfluoro(Benzylphosphonic Acid)s via polymer side chain phosphorylation - Elizabeth Salako; Matthew Thompson; Rong Jiang; Yong Gao (Journal of Fluorine Chemistry, 2024)

Assessment of water levels from 43 years of NOAA’s Coastal Ocean Reanalysis (CORA) for the Gulf of Mexico and East Coasts - Linta Rose; Matthew J. Widlansky; Xue Feng; Philip Thompson; Taylor G. Asher; Gregory Dusek; Brian Blanton; Richard A. Luettich; John Callahan; William Brooks; Analise Keeney; Jana Haddad; et al. (Frontiers in Marine Science, 2024)
Coastal water level information is crucial for understanding flood occurrences and changing risks. Here, we validate the preliminary version (0.9) of NOAA’s Coastal Ocean Reanalysis (CORA), which is a 43-year reanalysis (1979–2021) of hourly coastal water levels for the Gulf of Mexico and Atlantic Ocean (i.e., the Gulf and East Coast region, or GEC). CORA-GEC v0.9 was conducted by the Renaissance Computing Institute using the coupled ADCIRC+SWAN coastal circulation and wave model. The model uses an unstructured mesh of nodes with varying spatial resolution that averages 400 m near the coast and is much coarser in the open ocean. Water level variations associated with tides and meteorological forcing are explicitly modeled, while lower-frequency water level variations are included by dynamically assimilating observations from NOAA’s National Water Level Observation Network. We compare CORA to water level observations that were either assimilated or not, and find that the reanalysis generally performs better than a state-of-the-art global ocean reanalysis (GLORYS12) in capturing the variability on monthly, seasonal, and interannual timescales as well as the long-term trend. The variability of hourly non-tidal residuals is also shown to be well resolved in CORA when compared to water level observations. Lastly, we present a case study of extreme water levels and coastal inundations around Miami, Florida to demonstrate an application of CORA for studying flood risks. Our assessment suggests that NOAA’s CORA-GEC v0.9 provides valuable information on water levels and flooding occurrence from 1979–2021 in areas that are experiencing changes across multiple time scales. CORA potentially can enhance flood risk assessment along parts of the U.S. Coast that do not have historical water level observations.

Pharmacokinetic models for first-in-human dose selection of immune-activating products in oncology - Haleh Saber; Matthew D. Thompson; John K. Leighton (Regulatory Toxicology and Pharmacology, 2024)

Correction: Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh‑Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2024)

Understanding mechanisms of racial disparities in breast cancer: an assessment of screening and regular care in the Carolina Breast Cancer Study - Matthew R. Dunn; Eman M. Metwally; Sanah Vohra; Terry Hyslop; Louise M. Henderson; Katherine Reeder-Hayes; Caroline A. Thompson; Jennifer Elston Lafata; Melissa A. Troester; Eboneé N. Butler (Cancer Causes & Control, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Oral Drug Product Administration via Enteral Feeding Tubes: In Vitro Testing - Selina Wilson; Julianne Farabaugh; Yemin Liu; Zhao Liu; Rachel Meyers; Matthew Santangelo; Karen Thompson (The AAPS Journal, 2024)

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

Improved capabilities of global ocean reanalyses for analysing sea level variability near the Atlantic and Gulf of Mexico Coastal U.S. - Xue Feng; Matthew J. Widlansky; Magdalena A. Balmaseda; Hao Zuo; Claire M. Spillman; Grant Smith; Xiaoyu Long; Philip Thompson; Arun Kumar; Gregory Dusek; William Sweet (Frontiers in Marine Science, 2024)
Realistic representation of monthly sea level anomalies in coastal regions has been a challenge for global ocean reanalyses. This is especially the case in coastal regions where sea levels are influenced by western boundary currents such as near the U.S. Atlantic Coast and the Gulf of Mexico. For these regions, most ocean reanalyses compare poorly to observations. Problems in reanalyses include errors in data assimilation and horizontal resolutions that are too coarse to simulate energetic currents like the Gulf Stream and Loop Current System. However, model capabilities are advancing with improved data assimilation and higher resolution. Here, we show that some current-generation ocean reanalyses produce monthly sea level anomalies with improved skill when compared to satellite altimetry observations of sea surface heights. Using tide gauge observations for coastal verification, we find the highest skill associated with the GLORYS12 and HYCOM ocean reanalyses. Both systems assimilate altimetry observations and have eddy-resolving horizontal resolutions (1/12°). We found less skill in three other ocean reanalyses (ACCESS-S2, ORAS5, and ORAP6) with coarser, though still eddy-permitting, resolutions (1/4°). The operational reanalysis from ECMWF (ORAS5) and their pilot reanalysis (ORAP6) provide an interesting comparison because the latter assimilates altimetry globally and with more weight, as well as assimilating ocean observations over continental shelves. We find these attributes associated with improved skill near many tide gauges. We also assessed an older reanalysis (CFSR), which has the lowest skill likely due to its lower resolution (1/2°) and lack of altimetry assimilation. ACCESS-S2 likewise does not assimilate altimetry, although its skill is much better than CFSR and only somewhat lower than ORAS5. Since coastal flooding is influenced by sea level anomalies, the recent development of skilful ocean reanalyses on monthly timescales may be useful for better understanding the physical processes associated with flood risks.

A hyperspectral view of the nearshore Mississippi River Delta: Characterizing suspended particles in coastal wetlands using imaging spectroscopy - Joshua P. Harringmeyer; Nilotpal Ghosh; Matthew W. Weiser; David R. Thompson; Marc Simard; Steven E. Lohrenz; Cédric G. Fichot (Remote Sensing of Environment, 2024)

Trace element chemistry and strontium isotope ratios of atmospheric particulate matter reveal air quality impacts from mineral dust, urban pollution, and fireworks in the Wasatch Front, Utah, USA - Micah J. Marcy; Gregory T. Carling; Alyssa N. Thompson; Barry R. Bickmore; Stephen T. Nelson; Kevin A. Rey; Diego P. Fernandez; Matthew Heiner; Bradley R. Adams (Applied Geochemistry, 2024)

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

Cryopreservation of diverse symbiodiniaceae species: fatty acid profiles, growth and photosynthetic performance - Joseph Kihika; Susanna Wood; Lesley Rhodes; Kirsty Smith; Matthew Miller; Xavier Pochon; Lucy Thompson; Juliette Butler; Clint Oakley; Ken Ryan (Cryobiology, 2023)

Diabetes Mellitus Type 2 as a Risk Factor and Outcome Modifier for Cryptococcosis in HIV Negative, Non-transplant Patients, a Propensity Score Match Analysis - Vanessa M. Kung; Carolina Ferraz; Matthew Kennis; Carlos Franco-Paredes; Jose Tuells; Lilian Vargas Barahona; Leland Shapiro; George R. Thompson; Daniel B. Chastain; Andrés F. Henao-Martínez (Current Microbiology, 2023)

Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh-Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

On thresholds for controlling negative particle (PM2.5) readings in air quality reporting - Ningbo Jiang; Rinat Akter; Glenn Ross; Stephen White; John Kirkwood; Gunaratnam Gunashanhar; Scott Thompson; Matthew Riley; Merched Azzi (Environmental Monitoring and Assessment, 2023)
Ambient PM 2.5 (particles less than 2.5 μm in diameter) is monitored in many countries including Australia. Occasionally PM 2.5 instruments may report negative measurements, although in realty the ambient air can never contain negative amounts of particles. Some negative readings are caused by instrument faults or procedural errors, thus can be simply invalidated from air quality reporting. There are occasions, however, when negative readings occur due to other factors including technological or procedural limitations. Treatment of such negative data requires consideration of factors such as measurement uncertainty, instrument noise and risk for significant bias in air quality reporting. There is very limited documentation on handling negative PM 2.5 data in the literature. This paper demonstrates how a threshold is determined for controlling negative hourly PM 2.5 readings in the New South Wales (NSW) air quality data system. The investigation involved a review of thresholds used in different data systems and an assessment of instrument measurement uncertainties, zero air test data and impacts on key reporting statistics when applying different thresholds to historical datasets. The results show that a threshold of −10.0 μg/m 3 appears optimal for controlling negative PM 2.5 data in public reporting. This choice is consistent with the measurement uncertainty estimates and the zero air test data statistics calculated for the NSW Air Quality Monitoring Network, and is expected not to have significant impacts on key compliance reporting statistics such as data availability and annual average pollution levels. The analysis can be useful for air quality monitoring in other Australian jurisdictions or wider context.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Late Eocene to late Oligocene terrestrial climate and vegetation change in the western Tasmanian region - Michael Amoo; Ulrich Salzmann; Matthew J. Pound; Frida S. Hoem; Nick Thompson; Peter K. Bijl (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Wastewater surveillance uncovers regional diversity and dynamics of SARS-CoV-2 variants across nine states in the USA - Rafaela S. Fontenele; Yiyan Yang; Erin M. Driver; Arjun Magge; Simona Kraberger; Joy M. Custer; Keith Dufault-Thompson; Erin Cox; Melanie Engstrom Newell; Arvind Varsani; Rolf U. Halden; Matthew Scotch; et al. (Science of The Total Environment, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Wildfire Response: A System on the Brink? - Matthew P Thompson; Erin J Belval; Jude Bayham; David E Calkin; Crystal S Stonesifer; David Flores (Journal of Forestry, 2023)
Increasing wildfire activity, decreasing workforce capacity, and growing systemic strain may result in an interagency wildfire-response system less capable of protecting landscapes and communities. Further, increased workloads will likely increase hazards to fire personnel and amplify existing problems with recruitment and retention. In the face of elevated risks and degraded capacity, it is imperative that the wildfire-response system operate efficiently. Viable solutions are urgently needed that enable the system to do more with less and that manage not only for landscapes and communities but also the health and wellbeing of the fire personnel on whom the system relies. Achieving this will likely require rethinking how the interagency wildfire-response system can more adaptively and intelligently deploy fire personnel by leveraging enhanced logistics, operations, and proven fire analytics.

Demonstration of low-level biogenic fuel content using quench curve and direct liquid scintillation counting (LSC) methods - Charles G. Doll; Andrew E. Plymale; Matthew J. O'Hara; Christopher J. Thompson; Alan Cooper; Huamin Wang; Mariefel V. Olarte (Fuel, 2023)

What is the role of disturbance in catalyzing spatial shifts in forest composition and tree species biomass under climate change? - Yu Liang; Eric J. Gustafson; Hong S. He; Josep M. Serra‐Diaz; Matthew J. Duveneck; Jonathan R. Thompson (Global Change Biology, 2023)
Mounting evidence suggests that climate change will cause shifts of tree species range and abundance (biomass). Abundance changes under climate change are likely to occur prior to a detectable range shift. Disturbances are expected to directly affect tree species abundance and composition, and could profoundly influence tree species spatial distribution within a geographical region. However, how multiple disturbance regimes will interact with changing climate to alter the spatial distribution of species abundance remains unclear. We simulated such forest demographic processes using a forest landscape succession and disturbance model (LANDIS‐II) parameterized with forest inventory data in the northeastern United States. Our study incorporated climate change under a high‐emission future and disturbance regimes varying with gradients of intensities and spatial extents. The results suggest that disturbances catalyze changes in tree species abundance and composition under a changing climate, but the effects of disturbances differ by intensity and extent. Moderate disturbances and large extent disturbances have limited effects, while high‐intensity disturbances accelerate changes by removing cohorts of mid‐ and late‐successional species, creating opportunities for early‐successional species. High‐intensity disturbances result in the northern movement of early‐successional species and the southern movement of late‐successional species abundances. Our study is among the first to systematically investigate how disturbance extent and intensity interact to determine the spatial distribution of changes in species abundance and forest composition.

Toward Identifying the Critical Ecological Habitat of Larval Fishes: An Environmental DNA Window into Fisheries Management - Erin Satterthwaite; Andrew Allen; Robert Lampe; Zachary Gold; Andrew Thompson; Noelle Bowlin; Rasmus Swalethorp; Kelly Goodwin; Elliott Hazen; Steven Bograd; Stephanie Matthews; Brice Semmens (Oceanography, 2023)
Environmental DNA (eDNA)-based ecological co-occurrence networks can provide a valuable tool for fisheries and conservation management. In the past, it was nearly impossible to explore the microscopic world of larval fishes in one sampling event. Now, eDNA data and ecological co-occurrence network modeling provide windows into ecosystems that support larval fishes and upon which subsequent fisheries rely. Thus, there is great potential for eDNA methods coupled with ecological network analyses to provide a holistic understanding of community composition and species interactions and to develop indicators for fisheries and ecosystem-based management.

A Geospatial Approach to Improving Fish Species Detection in Maumee Bay, Lake Erie - Jessica Bowser; Andrew Briggs; Patricia Thompson; Matthew McLean; Anjanette Bowen (Fishes, 2022)
Maumee Bay of western Lake Erie is at high risk for invasion by aquatic invasive species due to large urban and suburban populations, commercial shipping traffic, recreational boating, and aquaculture ponds. The U.S. Fish and Wildlife Service’s Early Detection and Monitoring (EDM) program has been monitoring for new invasive species since 2013 and is continually looking to adapt sampling methods to improve efficiency to increase the chance of detecting new aquatic invasive species at low abundances. From 2013–2016, the program used a random sampling design in Maumee Bay with three gear types: boat electrofishing, paired fyke nets, and bottom trawling. Capture data from the initial three years was used to spatially explore fish species richness with the hot spot analysis (Getis-Ord Gi*) in ArcGIS. In 2017, targeted sites in areas with high species richness (hot spots) were added to the randomly sampled sites to determine if the addition of targeted sampling would increase fish species detection rates and detection of rare species. Results suggest that this hybrid sampling design improved sampling efficiency as species not detected or were rare in previous survey years were captured and species were detected at a faster rate (i.e., in less sampling effort), particularly for shallow-water gear types. Through exploring past data and experimenting with targeted sampling, the EDM program will continue to refine and adapt sampling efforts to improve efficiency and provide valuable knowledge for the early detection of aquatic invasive species. The use of geospatial techniques such as hot spot analysis is one approach fisheries researchers and managers can use to incorporate targeted sampling in a non-subjective way to improve species detection.

A novel statistical approach to predict seasonal high tide flooding - Gregory Dusek; William V. Sweet; Matthew J. Widlansky; Philip R. Thompson; John J. Marra (Frontiers in Marine Science, 2022)
Sea level rise is increasing the frequency of high tide flooding in coastal communities across the United States. Although the occurrence and severity of high-tide flooding will continue to increase, skillful prediction of high tide flooding on monthly-to-annual time horizons is lacking in most regions. Here, we present an approach to predict the daily likelihood of high tide flooding at coastal locations throughout the U.S. using a novel probabilistic modeling approach that relies on relative sea-level rise, tide predictions, and climatological non-tidal residuals as measured by NOAA tide gauges. A retrospective skill assessment using the climatological sea level information indicates that this approach is skillful at 61 out of 92 NOAA tide gauges where at least 10 high tide flood days occurred from 1997–2019. In this case, a flood day occurs when the observed water level exceeds the gauge-specific high tide flood threshold. For these 61 gauges, on average 35% of all floods are accurately predicted using this model, with over half of the floods accurately predicted at 18 gauges. The corresponding False-Alarm-Rate is less than 10% for all 61 gauges. Including mean sea level anomaly persistence at leads of 1 and 3 months further improves model skill in many locations, especially the U.S. Pacific Islands and West Coast. Model skill is shown to increase substantially with increasing sea level at nearly all locations as high tides more frequently exceed the high tide flooding threshold. Assuming an intermediate amount of relative sea level rise, the model will likely be skillful at 93 out of the 94 gauges projected to have regular flooding by 2040. These results demonstrate that this approach is viable to be incorporated into NOAA decision-support products to provide guidance on likely high tide flooding days. Further, the structure of the model will enable future incorporation of mean sea level anomaly predictions from numerical, statistical, andmachine learning forecast systems.

Mapping lesion, structural disconnection, and functional disconnection to symptoms in semantic aphasia - Nicholas E. Souter; Xiuyi Wang; Hannah Thompson; Katya Krieger-Redwood; Ajay D. Halai; Matthew A. Lambon Ralph; Michel Thiebaut de Schotten; Elizabeth Jefferies (Brain Structure and Function, 2022)
Patients with semantic aphasia have impaired control of semantic retrieval, often accompanied by executive dysfunction following left hemisphere stroke. Many but not all of these patients have damage to the left inferior frontal gyrus, important for semantic and cognitive control. Yet semantic and cognitive control networks are highly distributed, including posterior as well as anterior components. Accordingly, semantic aphasia might not only reflect local damage but also white matter structural and functional disconnection. Here, we characterise the lesions and predicted patterns of structural and functional disconnection in individuals with semantic aphasia and relate these effects to semantic and executive impairment. Impaired semantic cognition was associated with infarction in distributed left-hemisphere regions, including in the left anterior inferior frontal and posterior temporal cortex. Lesions were associated with executive dysfunction within a set of adjacent but distinct left frontoparietal clusters. Performance on executive tasks was also associated with interhemispheric structural disconnection across the corpus callosum. In contrast, poor semantic cognition was associated with small left-lateralized structurally disconnected clusters, including in the left posterior temporal cortex. Little insight was gained from functional disconnection symptom mapping. These results demonstrate that while left-lateralized semantic and executive control regions are often damaged together in stroke aphasia, these deficits are associated with distinct patterns of structural disconnection, consistent with the bilateral nature of executive control and the left-lateralized yet distributed semantic control network.

Conceptualizing a probabilistic risk and loss assessment framework for wildfires - Negar Elhami-Khorasani; Hamed Ebrahimian; Lawrence Buja; Susan L. Cutter; Branko Kosovic; Neil Lareau; Brian J. Meacham; Eric Rowell; Ertugrul Taciroglu; Matthew P. Thompson; Adam C. Watts (Natural Hazards, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A randomised, open-label, cross-over clinical study to evaluate the pharmacokinetic, pharmacodynamic and safety and tolerability profiles of tobacco-free oral nicotine pouches relative to cigarettes - Fiona Chapman; Simon McDermott; Kathryn Rudd; Victoria Taverner; Matthew Stevenson; Nveed Chaudhary; Kerstin Reichmann; Joseph Thompson; Thomas Nahde; Grant O’Connell (Psychopharmacology, 2022)
Rationale Tobacco harm reduction (THR) involves encouraging adult smokers who would otherwise continue to smoke to transition to less harmful forms of nicotine delivery. These products must offer adult smokers reduced exposure to chemicals associated with tobacco combustion, satisfactory blood plasma nicotine levels and serve as an acceptable alternative. The most recent THR innovation is tobacco-free oral nicotine pouches. Objectives This study aimed to compare pharmacokinetic, pharmacodynamic and safety and tolerability profiles of two nicotine pouch variants (ZoneX #2 (5.8 mg nicotine/pouch); ZoneX #3 (10.1 mg nicotine/pouch)) with cigarette to assess the pouches’ THR potential. Methods This was a controlled use, randomised, open-label, cross-over clinical study with 24 healthy adult traditional tobacco users. Pharmacokinetic (plasma nicotine levels; up to 8 h post-use), pharmacodynamic (urge to smoke, product liking; up to 4 h post-use) and short-term safety and tolerability profiles were assessed. Results Distinct nicotine pouch pharmacokinetic profiles indicated nicotine absorption via the oral mucosa. Plasma nicotine levels were lower, and time to peak slower, for the nicotine pouches compared to cigarette ( C max cigarette: 11.6 ng/ml vs. #2: 5.2 ng/ml, p < 0.0001; #3: 7.9 ng/ml, p < 0.0003) ( T max cigarette: 8.6 min vs. #2: 26 min; #3: 22 min). All products effectively reduced subjects’ urge to smoke and presented favourable product liking scores; nicotine pouches were also well tolerated following short-term use (no serious adverse events). Conclusions Overall, the assessed ZoneX nicotine pouches may offer an acceptable alternative for adult smokers to achieve satisfactory levels of nicotine delivery and, based on the pharmacokinetic parameters and under the study conditions, likely have a lower abuse liability and addictive potential for current adult smokers compared to continued cigarette smoking. Clinical trial identifier: NCT04891406 (clinicaltrials.gov).

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Limits to the generalizability of resting-state functional magnetic resonance imaging studies of youth: An examination of ABCD Study® baseline data - Kelly T. Cosgrove; Timothy J. McDermott; Evan J. White; Matthew W. Mosconi; Wesley K. Thompson; Martin P. Paulus; Carlos Cardenas-Iniguez; Robin L. Aupperle (Brain Imaging and Behavior, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Novel DNA‐based in situ hybridization method to detect Desmozoon lepeophtherii in Atlantic salmon tissues - Ana Herrero; Oswaldo Palenzuela; Hamish Rodger; Chris Matthews; Mar Marcos‐López; James E. Bron; Mark P. Dagleish; Kim D. Thompson (Journal of Fish Diseases, 2022)
The microsporidian Desmozoon lepeophtherii Freeman and Sommerville, 2009 is considered significant in the pathogenesis of gill disease in Atlantic salmon ( Salmo salar Linnaeus, 1758). Due to the difficulty in detecting D. lepeophtherii in tissue sections, infections are normally diagnosed by molecular methods, routine haematoxylin and eosin (H&E) stained gill tissue sections and the use of other histochemical stains and labels to confirm the presence of spores. An in situ hybridization (ISH) protocol specific for D. lepeophtherii was developed using DIG‐labelled oligonucleotide probes. Diseased Atlantic salmon gills were analysed by ISH, calcofluor white (CW) and H&E. All methods showed high levels of specificity (100%) in their ability to detect D. lepeophtherii , but the sensitivity was higher with ISH (92%), compared with CW (64%) and the presence of microvesicles on H&E stained sections (52%). High levels of D. lepeophtherii spores were significantly associated ( p D. lepeophtherii ‐associated pathology in the gills, with Ct values below 19 and over 100 microsporidia/10 mm 2 of gill tissue (from the ISH counts) seemingly necessary for the development of microvesicles. The ISH method has the advantage over other histological techniques in that it allows all life stages of the microsporidian to be detected in infected salmon gill tissue sections.

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Rapid spatial expansion and population increase of invasive lionfish (Pterois spp.) observed on natural habitats in the northern Gulf of Mexico - Matthew D. Campbell; Adam G. Pollack; Kevin Thompson; Ted Switzer; William B. Driggers; Eric R. Hoffmayer; Sean Keenan; Chris Gardner; David Hanisko; Kevin R. Rademacher; Kate Overly (Biological Invasions, 2022)

Untangling local and remote influences in two major petrel habitats in the oligotrophic Southern Ocean - Daniel C. Jones; Filipe R. Ceia; Eugene Murphy; Karine Delord; Robert W. Furness; Ariane Verdy; Matthew Mazloff; Richard A. Phillips; Paul M. Sagar; Jean‐Baptiste Sallée; Ben Schreiber; David R. Thompson; et al. (Global Change Biology, 2021)
Ocean circulation connects geographically distinct ecosystems across a wide range of spatial and temporal scales via exchanges of physical and biogeochemical properties. Remote oceanographic processes can be especially important for ecosystems in the Southern Ocean, where the Antarctic Circumpolar Current transports properties across ocean basins through both advection and mixing. Recent tracking studies have indicated the existence of two large‐scale, open ocean habitats in the Southern Ocean used by grey petrels ( Procellaria cinerea ) from two populations (i.e., Kerguelen and Antipodes islands) during their nonbreeding season for extended periods during austral summer (i.e., October to February). In this work, we use a novel combination of large‐scale oceanographic observations, surface drifter data, satellite‐derived primary productivity, numerical adjoint sensitivity experiments, and output from a biogeochemical state estimate to examine local and remote influences on these grey petrel habitats. Our aim is to understand the oceanographic features that control these isolated foraging areas and to evaluate their ecological value as oligotrophic open ocean habitats. We estimate the minimum local primary productivity required to support these populations to be much

Estimating fine‐scale movement rates and habitat preferences using multiple data sources - James T. Thorson; Steven J. Barbeaux; Daniel R. Goethel; Kelly A. Kearney; Edward A. Laman; Julie K. Nielsen; Matthew R. Siskey; Kevin Siwicke; Grant G. Thompson (Fish and Fisheries, 2021)
Fisheries scientists and managers must track rapid shifts in fish spatial distribution to mitigate stakeholder conflict and optimize survey designs, and these spatial shifts result in part from animal movement. Information regarding animal movement can be obtained from selection experiments, tagging studies, flux through movement gates (e.g. acoustic arrays), fishery catch‐per‐unit effort (CPUE), resource surveys and genetic/chemical markers. However, there are few accessible approaches to combine these data types while accounting for spatially correlated residual patterns. We therefore discuss a movement model involving diffusion (random movement), taxis (movement towards preferred habitat) and advection (passive drift following ocean currents). We specifically outline how these movement processes can be fitted to data while discretizing space and time and estimating non‐linear habitat preferences using environmental layers as well as spatial process errors. Finally, we introduce an R package, ATM, by fitting the model to bottom trawl survey, longline fishery and tagging data for Pacific cod ( Gadus macrocephalus , Gadidae) in the Bering Sea during winter/summer seasons from 1982 to 2019. Combining data types predicts an increasing proportion of cod residing in the northern Bering Sea from 2013 to 2019, and estimates are informative in a recent stock assessment model. We fit sensitivity analyses by dropping tag, survey or fishery data, and this analysis shows that tagging data are necessary to identify diffusion rates, while survey data are informative about movement among biogeographic strata. This “hybrid” species distribution model can help explain poleward movement, project distributions under future climate conditions and evaluate alternative tag‐deployment scenarios to optimize tagging designs.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Emergence of an evolutionary innovation: Gene expression differences associated with the transition between oviparity and viviparity - Charles S. P. Foster; Michael B. Thompson; James U. Van Dyke; Matthew C. Brandley; Camilla M. Whittington (Molecular Ecology, 2020)
Our understanding of the evolution of complex biological traits is greatly advanced by examining taxa with intermediate phenotypes. The transition from oviparity (egg‐laying) to viviparity (live‐bearing) has occurred independently in many animal lineages, but there are few phenotypic intermediates. The lizard Saiphos equalis exhibits bimodal reproduction, with some viviparous populations, and other oviparous populations with long egg‐retention, a rare trait where most of embryonic development occurs inside the mother prior to late ovipositioning. We posit that oviparous S. equalis represent an intermediate form between “true” oviparity and viviparity. We used transcriptomics to compare uterine gene expression in these two phenotypes, and provide a molecular model for the genetic control and evolution of reproductive mode. Many genes are differentially expressed throughout the reproductive cycle of both phenotypes, which have clearly different gene expression profiles overall. The differentially expressed genes within oviparous and viviparous individuals have broadly similar biological functions putatively important for sustaining embryos, including uterine remodelling, respiratory gas and water exchange, and immune regulation. These functional similarities indicate either that long egg‐retention is an exaptation for viviparity, or might reflect parallel evolution of similar gravidity‐related changes in gene expression in long egg‐retention oviparity. In contrast, gene expression changes across the reproductive cycle of long egg‐retaining oviparous S. equalis are dramatically different from those of “true” oviparous skinks (such as Lampropholis guichenoti ), supporting our assertion that oviparous S. equalis exhibit an intermediate phenotype between “true” oviparity and viviparity.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Risk Management and Analytics in Wildfire Response - Matthew P. Thompson; Yu Wei; David E. Calkin; Christopher D. O’Connor; Christopher J. Dunn; Nathaniel M. Anderson; John S. Hogland (Current Forestry Reports, 2019)
Purpose of Review The objectives of this paper are to briefly review basic risk management and analytics concepts, describe their nexus in relation to wildfire response, demonstrate real-world application of analytics to support response decisions and organizational learning, and outline an analytics strategy for the future. Recent Findings Analytics can improve decision-making and organizational performance across a variety of areas from sports to business to real-time emergency response. A lack of robust descriptive analytics on wildfire incident response effectiveness is a bottleneck for developing operationally relevant and empirically credible predictive and prescriptive analytics to inform and guide strategic response decisions. Capitalizing on technology such as automated resource tracking and machine learning algorithms can help bridge gaps between monitoring, learning, and data-driven decision-making. Summary By investing in better collection, documentation, archiving, and analysis of operational data on response effectiveness, fire management organizations can promote systematic learning and provide a better evidence base to support response decisions. We describe an analytics management framework that can provide structure to help deploy analytics within organizations, and provide real-world examples of advanced fire analytics applied in the USA. To fully capitalize on the potential of analytics, organizations may need to catalyze cultural shifts that cultivate stronger appreciation for data-driven decision processes, and develop informed skeptics that effectively balance both judgment and analysis in decision-making.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

First Report of the Presence of Slugs in a Commercial Potato Storage Facility in the United States - Silvia I. Rondon; Daniel I. Thompson; Matthew L. Klein; Rory J. Mc Donnell (American Journal of Potato Research, 2019)

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts - Camille Mellin; Samuel Matthews; Kenneth R.N. Anthony; Stuart C. Brown; M. Julian Caley; Kerryn A. Johns; Kate Osborne; Marjetta Puotinen; Angus Thompson; Nicholas H. Wolff; Damien A. Fordham; M. Aaron MacNeil (Global Change Biology, 2019)
In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐thorns starfish ( Acanthaster cf. solaris ), and tropical cyclones. Our projections reconstruct coral cover trajectories between 1996 and 2017 over a total reef area of 14,780 km 2 , predicting a mean annual coral loss of −0.67%/year mostly due to the impact of cyclones, followed by starfish outbreaks and coral bleaching. Coral growth rate was the highest for outer shelf coral communities characterized by digitate and tabulate Acropora spp. and exposed to low seasonal variations in salinity and sea surface temperature, and the lowest for inner‐shelf communities exposed to reduced water quality. We show that coral resilience (defined as the net effect of resistance and recovery following disturbance) was negatively related to the frequency of river plume conditions, and to reef accessibility to a lesser extent. Surprisingly, reef resilience was substantially lower within no‐take marine protected areas, however this difference was mostly driven by the effect of water quality. Our model provides a new validated, spatially explicit platform for identifying the reefs that face the greatest risk of biodiversity loss, and those that have the highest chances to persist under increasing disturbance regimes.

Changes in sociality of butterflyfishes linked to population declines and coral loss - Cassandra A. Thompson; Samuel Matthews; Andrew S. Hoey; Morgan S. Pratchett (Coral Reefs, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

Textural evolution of perovskite in the Afrikanda alkaline–ultramafic complex, Kola Peninsula, Russia - Naomi J. Potter; Matthew R. M. Ferguson; Vadim S. Kamenetsky; Anton R. Chakhmouradian; Victor V. Sharygin; Jay M. Thompson; Karsten Goemann (Contributions to Mineralogy and Petrology, 2018)

Longitudinal Preterm Cerebellar Volume: Perinatal and Neurodevelopmental Outcome Associations - Lillian G. Matthews; T. E. Inder; L. Pascoe; K. Kapur; K. J. Lee; B. B. Monson; L. W. Doyle; D. K. Thompson; P. J. Anderson (The Cerebellum, 2018)

Clinical Translation of the LevelCheck Decision Support Algorithm for Target Localization in Spine Surgery - Amir Manbachi; Tharindu De Silva; Ali Uneri; Matthew Jacobson; Joseph Goerres; Michael Ketcha; Runze Han; Nafi Aygun; David Thompson; Xiaobu Ye; Sebastian Vogt; Gerhard Kleinszig; et al. (Annals of Biomedical Engineering, 2018)

The metabolic fate of fenclozic acid in chimeric mice with a humanized liver - Anja Ekdahl; Lars Weidolf; Matthew Baginski; Yoshio Morikawa; Richard A. Thompson; Ian D. Wilson (Archives of Toxicology, 2018)

Parsing the neural correlates of anxious apprehension and anxious arousal in the grey-matter of healthy youth - Peter J. Castagna; Scott Roye; Matthew Calamia; Joshua Owens-French; Thompson E. Davis; Steven G. Greening (Brain Imaging and Behavior, 2018)

Rethinking the Wildland Fire Management System - Matthew P Thompson; Donald G MacGregor; Christopher J Dunn; David E Calkin; John Phipps (Journal of Forestry, 2018)

Liposomal Amphotericin B as Monotherapy in Relapsed Coccidioidal Meningitis - Ethan R. Stewart; Matthew L. Eldridge; Ian McHardy; Stuart H. Cohen; George R. Thompson (Mycopathologia, 2018)

How disturbance, competition, and dispersal interact to prevent tree range boundaries from keeping pace with climate change - Yu Liang; Matthew J. Duveneck; Eric J. Gustafson; Josep M. Serra‐Diaz; Jonathan R. Thompson (Global Change Biology, 2018)
Climate change is expected to cause geographic shifts in tree species' ranges, but such shifts may not keep pace with climate changes because seed dispersal distances are often limited and competition‐induced changes in community composition can be relatively slow. Disturbances may speed changes in community composition, but the interactions among climate change, disturbance and competitive interactions to produce range shifts are poorly understood. We used a physiologically based mechanistic landscape model to study these interactions in the northeastern United States. We designed a series of disturbance scenarios to represent varied disturbance regimes in terms of both disturbance extent and intensity. We simulated forest succession by incorporating climate change under a high‐emissions future, disturbances, seed dispersal, and competition using the landscape model parameterized with forest inventory data. Tree species range boundary shifts in the next century were quantified as the change in the location of the 5th (the trailing edge) and 95th (the leading edge) percentiles of the spatial distribution of simulated species. Simulated tree species range boundary shifts in New England over the next century were far below (usually

Erratum to: Trends in the classical biological control of insect pests by insects: an update of the BIOCAT database - Matthew J. W. Cock; Sean T. Murphy; Moses T. K. Kairo; Emma Thompson; Rebecca J. Murphy; Antonio W. Francis (BioControl, 2017)

Wildfire effects on physiological properties in conifers of central Idaho forests, USA - Matthew T. C. Thompson; Akihiro Koyama; Kathleen L. Kavanagh (Trees, 2017)

The effect of grapefruits ( Citrus paradisi ) on body weight and cardiovascular risk factors: A systematic review and meta-analysis of randomized clinical trials - Igho Onakpoya; Jack O'Sullivan; Carl Heneghan; Matthew Thompson (Critical Reviews in Food Science and Nutrition, 2017)

Trends in the classical biological control of insect pests by insects: an update of the BIOCAT database - Matthew J. W. Cock; Sean T. Murphy; Moses T. K. Kairo; Emma Thompson; Rebecca J. Murphy; Antonio W. Francis (BioControl, 2016)

Acute high-intensity interval rowing increases thrombin generation in healthy men - Matthew J. Sedgwick; Matthew Thompson; Jack Garnham; Alice E. Thackray; Laura A. Barrett; Matthew Powis; David J. Stensel (European Journal of Applied Physiology, 2016)

Integrating Pixel- and Polygon-Based Approaches to Wildfire Risk Assessment: Application to a High-Value Watershed on the Pike and San Isabel National Forests, Colorado, USA - Matthew P. Thompson; Julie W. Gilbertson-Day; Joe H. Scott (Environmental Modeling & Assessment, 2016)

Errors on interrupter tasks presented during spatial and verbal working memory performance are linearly linked to large-scale functional network connectivity in high temporal resolution resting state fMRI - Matthew Evan Magnuson; Garth John Thompson; Hillary Schwarb; Wen-Ju Pan; Andy McKinley; Eric H. Schumacher; Shella Dawn Keilholz (Brain Imaging and Behavior, 2015)

Dietary nitrate improves sprint performance and cognitive function during prolonged intermittent exercise - Christopher Thompson; Lee J. Wylie; Jonathan Fulford; James Kelly; Matthew I. Black; Sinead T. J. McDonagh; Asker E. Jeukendrup; Anni Vanhatalo; Andrew M. Jones (European Journal of Applied Physiology, 2015)

African-American Breast Cancer Survivors Participating in a Breast Cancer Support Group: Translating Research into Practice - Anjanette A. Wells; Lauren Gulbas; Vetta Sanders-Thompson; En-Jung Shon; Matthew W. Kreuter (Journal of Cancer Education, 2014)

Genetic analysis of quantitative phenotypes in AD and MCI: imaging, cognition and biomarkers - Li Shen; Paul M. Thompson; Steven G. Potkin; Lars Bertram; Lindsay A. Farrer; Tatiana M. Foroud; Robert C. Green; Xiaolan Hu; Matthew J. Huentelman; Sungeun Kim; John S. K. Kauwe; Qingqin Li; et al. (Brain Imaging and Behavior, 2014)

Best Practices for the Development, Scale-up, and Post-approval Change Control of IR and MR Dosage Forms in the Current Quality-by-Design Paradigm - Glenn A. Van Buskirk; Satish Asotra; Christopher Balducci; Prabir Basu; Gerald DiDonato; Angelica Dorantes; W. Mark Eickhoff; Tapash Ghosh; Mario A. González; Theresa Henry; Matthew Howard; Jason Kamm; et al. (AAPS PharmSciTech, 2014)

Viral over-expression of D1 dopamine receptors in the prefrontal cortex increase high-risk behaviors in adults: Comparison with adolescents - Kai C. Sonntag; Heather C. Brenhouse; Nadja Freund; Britta S. Thompson; Matthew Puhl; Susan L. Andersen (Psychopharmacology, 2014)

Prohibitin (PHB) inhibits apoptosis in rat granulosa cells (GCs) through the extracellular signal-regulated kinase 1/2 (ERK1/2) and the Bcl family of proteins - Indrajit Chowdhury; Winston E. Thompson; Crystal Welch; Kelwyn Thomas; Roland Matthews (Apoptosis, 2013)

A polygon-based modeling approach to assess exposure of resources and assets to wildfire - Matthew P. Thompson; Joe Scott; Jeffrey D. Kaiden; Julie W. Gilbertson-Day (Natural Hazards, 2013)

Probabilistic assessment of wildfire hazard and municipal watershed exposure - Joe Scott; Don Helmbrecht; Matthew P. Thompson; David E. Calkin; Kate Marcille (Natural Hazards, 2012)

Mikrobielle Ökologie des Roten Meeres - Uli Stingl; David Kamanda Ngugi; Luke Thompson; Andre Antunes; Matthew Cahill (BIOspektrum, 2012)

Use of partition coefficients in flow-limited physiologically-based pharmacokinetic modeling - Matthew D. Thompson; Daniel A. Beard; Fan Wu (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Integrated national-scale assessment of wildfire risk to human and ecological values - Matthew P. Thompson; David E. Calkin; Mark A. Finney; Alan A. Ager; Julie W. Gilbertson-Day (Stochastic Environmental Research and Risk Assessment, 2011)

Neuromuscular function following prolonged intense self-paced exercise in hot climatic conditions - Julien D. Périard; Matthew N. Cramer; Phillip G. Chapman; Corinne Caillaud; Martin W. Thompson (European Journal of Applied Physiology, 2011)

Advancing effects analysis for integrated, large-scale wildfire risk assessment - Matthew P. Thompson; David E. Calkin; Julie W. Gilbertson-Day; Alan A. Ager (Environmental Monitoring and Assessment, 2011)

Development of appropriate equations for physiologically based pharmacokinetic modeling of permeability-limited and flow-limited transport - Matthew D. Thompson; Daniel A. Beard (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

A Real-Time Risk Assessment Tool Supporting Wildland Fire Decisionmaking - David E. Calkin; Matthew P. Thompson; Mark A. Finney; Kevin D. Hyde (Journal of Forestry, 2011)
Development of appropriate management strategies for escaped wildland fires is complex. Fire managers need the ability to identify, in real time, the likelihood that wildfire will affect valuable developed and natural resources (e.g., private structures, public infrastructure, and natural and cultural resources). These determinations help guide where and when aggressive suppression is required to protect values and when fire may be allowed to burn to enhance ecosystem conditions. This article describes the primary components of the Wildland Fire Decision Support System (WFDSS), a geospatial decision support system developed by the US Forest Service. WFDSS provides state-of-the-art wildfire risk analysis, decision documentation, and long-term implementation planning. In particular, we describe how the two primary decision support analysis components of WFDSS, Fire Spread Probability (fire behavior) and Rapid Assessment of Values at Risk (resource assessment), fit into the current state of risk assessment tools for wildfire suppression decisionmaking.

Degradation of sulfide by dehaloperoxidase-hemoglobin from Amphitrite ornata - Francesco P. Nicoletti; Matthew K. Thompson; Stefan Franzen; Giulietta Smulevich (JBIC Journal of Biological Inorganic Chemistry, 2011)

AKT1 polymorphisms are associated with risk for metabolic syndrome - Joseph M. Devaney; Heather Gordish-Dressman; Brennan T. Harmon; Margaret K. Bradbury; Stephanie A. Devaney; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Thomas B. Price; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; et al. (Human Genetics, 2011)

Exploring Environmental and Economic Trade-offs Associated with Aggregate Recycling from Decommissioned Forest Roads - Matthew P. Thompson; John Sessions (Environmental Modeling & Assessment, 2010)

Evaluation of data-driven network analysis approaches for functional connectivity MRI - Shella D. Keilholz; Matthew Magnuson; Garth Thompson (Brain Structure and Function, 2010)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Synthesis of “Difficult” Fluorescence Quenched Substrates of Granzyme C - Susan E. Northfield; Kade D. Roberts; Simon J. Mountford; Richard A. Hughes; Dion Kaiserman; Matthew Mangan; Robert N. Pike; Phillip I. Bird; Philip E. Thompson (International Journal of Peptide Research and Therapeutics, 2010)

A polymorphism near IGF1 is associated with body composition and muscle function in women from the Health, Aging, and Body Composition Study - Matthew C. Kostek; Joseph M. Devaney; Heather Gordish-Dressman; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; Linda S. Pescatello; Paul S. Visich; Robert F. Zoeller; et al. (European Journal of Applied Physiology, 2010)

The Albedo Effect and Forest Carbon Offset Design - Matthew Thompson; Darius Adams; K. Norman Johnson (Journal of Forestry, 2009)
Forestry and land-use change are often considered in the context of a greenhouse gas cap-and-trade program, in recognition of their influence on net carbon flux and their ability to mitigate climate change via increased carbon sequestration. The climatic impacts of forests are not limited to atmospheric greenhouse gas concentrations, however, and a growing body of research suggests that albedo-related climatic changes stemming from land-use change may diminish or counteract the climatic benefits of sequestration. Because forests are generally darker than bare or agricultural land they absorb relatively more solar radiation, which may exert a local warming influence. This phenomenon is known as the “albedo effect.” Thus, a “carbon-only” accounting approach that ignores albedo impacts can significantly overestimate the climatic benefit of offsets, in particular, afforestation. In the worst case this could result in a forest offset actually contributing to warming and, in general, may reduce the environmental effectiveness of some forest offsets. Therefore a cap-and-trade system design question is whether to recognize the albedo effect into forest offset accounting frameworks. We propose that forest offset design moves toward a “carbon-equivalent” accounting approach that aggregates the climatic impacts of sequestration and of surface albedo when evaluating forest offset projects. This change would result in climate mitigation efforts taking a more targeted geographic approach that emphasizes maintaining or increasing forest cover in the tropics, and that avoids afforestation in boreal and high-latitude temperate regions. Currently developing regional cap-and-trade systems in North America, however, give afforestation projects priority for offset consideration. By staying on the current path, efforts in these initiatives directed toward forest offsets may be inefficient or ineffective and, at worst, counterproductive, in large parts of the area they cover. Incorporating both carbon and albedo effects into policymaking will lead to more informed and effective forest offset design.

ATF3 transcription factor and its emerging roles in immunity and cancer - Matthew R. Thompson; Dakang Xu; Bryan R. G. Williams (Journal of Molecular Medicine, 2009)

The Potential for New Understandings of Normal and Abnormal Cognition by Integration of Neuroimaging and Behavioral Data: Not an Exercise in Carrying Coals to Newcastle - P. T. Michie; T. W. Budd; W. R. Fulham; M. E. Hughes; S. Jamadar; P. Johnston; F. Karayanidis; N. Matthews; P. E. Rasser; U. Schall; P. M. Thompson; J. Todd; et al. (Brain Imaging and Behavior, 2008)

Physical map of two tammar wallaby chromosomes: A strategy for mapping in non-model mammals - Janine E. Deakin; Edda Koina; Paul D. Waters; Ruth Doherty; Vidushi S. Patel; Margaret L. Delbridge; Bianca Dobson; James Fong; Yanqiu Hu; Cecilia van den Hurk; Andrew J. Pask; Geoff Shaw; et al. (Chromosome Research, 2008)

Optimal Policies for Aggregate Recycling from Decommissioned Forest Roads - Matthew Thompson; John Sessions (Environmental Management, 2008)

Impairment of movement-associated brain deactivation in multiple sclerosis: further evidence for a functional pathology of interhemispheric neuronal inhibition - S. C. Manson; C. Wegner; M. Filippi; F. Barkhof; C. Beckmann; O. Ciccarelli; N. De Stefano; Christian Enzinger; F. Fazekas; F. Agosta; A. Gass; J. Hirsch; et al. (Experimental Brain Research, 2008)

Exploring the Vast Diversity of Marine Viruses - Mya Breitbart; Luke Thompson; Curtis Suttle; Matthew Sullivan (Oceanography, 2007)

Identifying brain regions for integrative sensorimotor processing with ankle movements - O. Ciccarelli; A. T. Toosy; J. F. Marsden; C. M. Wheeler-Kingshott; C. Sahyoun; P. M. Matthews; D. H. Miller; A. J. Thompson (Experimental Brain Research, 2005)

Understanding the Hydraulics of Porous Pipes: Tradeoffs Between Water Uptake and Root Length Utilization - Maciej A. Zwieniecki; Matthew V. Thompson; N. Michele Holbrook (Journal of Plant Growth Regulation, 2002)

Incidence of hybridization between Atlantic salmon, Salmo salar L., and brown trout, Salmo trutta L., in Ireland - M. A. Matthews; W. R. Poole; C. E. Thompson; J. McKillen; A. Ferguson; K. Hindar; K. F. Wheelan (Fisheries Management and Ecology, 2000)
The substantial growth of the farmed salmon industry in Europe since the 1970s has highlighted concerns regarding the genetic impact of escaped farmed salmon on wild salmonid stocks. High incidences of salmon × trout hybrids have been recorded in rivers situated near intensive salmon farming in Norway and Scotland, which may be indicative of a breakdown in reproductive isolation between salmon, Salmo salar L., and brown trout, Salmo trutta L. In the present study, salmonid fry and 0+ parr were collected from rivers in western Ireland. Allozyme and minisatellite DNA analysis were carried out on fry to determine the frequency of F1 hybrids from 10 rivers located within 38 km of salmon farms and three rivers at least 80 km from salmon farms. A total of 49 hybrids were recorded from 4135 salmonid fry (frequency = 1.2%). Mitochondrial DNA analysis showed that all hybrids arose from Atlantic salmon female × brown trout male crosses. Hybrid parr were recorded from one of the low‐risk rivers (1.0%), but were present in seven out of the 10 catchments located within 38 km of salmon farms, with frequencies ranging from 0.7% to 3.1%. The results of the present survey, which represents the first extensive record of the levels of salmon‐trout hybridization in Ireland, are discussed in relation to the continued growth of salmon farming in this country.

Impulse response functions of terrestrial carbon cycle models: method and application - Matthew V. Thompson; James T. Randerson (Global Change Biology, 1999)
To provide a common currency for model comparison, validation and manipulation, we suggest and describe the use of impulse response functions , a concept well‐developed in other fields, but only partially developed for use in terrestrial carbon cycle modelling. In this paper, we describe the derivation of impulse response functions, and then examine (i) the dynamics of a simple five‐box biosphere carbon model; (ii) the dynamics of the CASA biosphere model, a spatially explicit NPP and soil carbon biogeochemistry model; and (iii) various diagnostics of the two models, including the latitudinal distribution of mean age, mean residence time and turnover time. We also (i) deconvolve the past history of terrestrial NPP from an estimate of past carbon sequestration using a derived impulse response function to test the performance of impulse response functions during periods of historical climate change; (ii) convolve impulse response functions from both the simple five‐box model and the CASA model against a historical record of atmospheric δ 13 C to estimate the size of the terrestrial 13 C isotopic disequilibrium; and (iii) convolve the same impulse response functions against a historical record of atmospheric 14 C to estimate the 14 C content and isotopic disequilibrium of the terrestrial biosphere at the 1° × 1° scale. Given their utility in model comparison, and the fact that they facilitate a number of numerical calculations that are difficult to perform with the complex carbon turnover models from which they are derived, we strongly urge the inclusion of impulse response functions as a diagnostic of the perturbation response of terrestrial carbon cycle models.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Olfaction in Persons with Alzheimer's Disease - Matthew D. Thompson; Kathleen Knee; Charles J. Golden (Neuropsychology Review, 1998)